Injustice during Night Work for Female Employees: A Lesson from Samarinda, Indonesia - Rio Arif Pratama; Bayu Prasetyo; Asnawi Mubarok; Ikhwanul Muslim (Indonesian Journal of Law and Economics Review, 2019)
Night working rules are legal provisions that give rights to female workers who work from 23:00 p.m.to 07:00 a.m.provided by employers. Night working rules for women have certain characteristics of potential hazards which are different from other profession. This study aims to determine the effectiveness of night working rules for female workers in Samarinda City. The specific target to be achieved in this study is to identify company that employs female workers from 23:00 p.m. to 07:00 a.m. and to review the role of labor inspectors in enforcing night working rules for female workers in Samarinda City. The method of this study is empirical legal research method which is analyzed qualitatively. The results of the study will be described analytically. The results of this study found that there were many violations of the night working rules, besides that female workers did not know what rights they should have gotten from their employers. The role of labor inspectors is still ineffective, even in some places there were some companies which night working rules had not been supervised by labor inspector. The implications of this research will be submitted to the Department of Manpower and Transmigration of East Kalimantan Province as a contribution of research information on the effectiveness of night working rules for female workers in Samarinda City.